Metode Tartila sebagai alternatif pembelajaran membaca Al-Quran di TPQ al-Hidayah Miftahul Ulum II Bekacak bangil: Metode Tartila sebagai alternatif pembelajaran membaca Al-Quran di TPQ al-Hidayah Miftahul Ulum II bekacak bangil - Julvan Vebianto; M. Jamhuri (al-Iltizam: Jurnal Pendidikan Agama Islam, 2025)
The Tartila method is one of the alternative methods in learning to read the Qur'an applied at TPQ al-Hidayah Miftahul Ulum II Bekacak, Bangil. The Tartila method is one of the methods of learning to read the Qur'an that emphasizes aspects of fluency (fasahah), accuracy of machraj, and the application of tajweed rules in stages. This study aims to analyze the effectiveness of the Tartila method in improving the ability to read al-Qur'an of students, as well as identifying obstacles faced in the learning process. Using a descriptive qualitative approach, this research involves direct observation, semi-structured interviews with educators and santri guardians, as well as documentation studies of students' learning outcomes. The results showed that the Tartila method was able to improve students' fluency, machraj accuracy, and understanding of tajweed. Learning is done classically with a gradual evaluation system. However, some of the obstacles faced include differences in the ability of students, the lack of involvement of educators, and the lack of support from santri guardians for religious education. Thus, efforts are needed to optimize this method to be more effective in producing a Qur'anic generation.